2011
DOI: 10.1016/j.tvjl.2010.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Expression of urocortin peptides in canine myocardium and plasma

Abstract: Urocortin (Ucn) peptides are the endogenous ligands for the corticotropin-releasing factor type 2 receptor (CRFR2). They have potentially important roles in cardiovascular physiology in health and disease, and show promise as therapeutics for congestive heart failure. Analysis of canine heart tissue showed mRNA expression of Ucn 1, Ucn 3 and CRFR2 in all heart chambers. Immunohistochemistry also demonstrated Ucn 1 and 3 expression in cardiomyocytes. To assess the potential usefulness of circulating Ucns as mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…CRF and urocortins also have cardioprotective effects that are mediated by cardiac CRF 2 receptors [ 67 ]. Urocortins 1, 2, and 3 are present in the heart, with the abundant expression of urocortins 2 and 3 in myocardium [ 68 ]. Urocortins are cardioprotective when added to post-ischemic/hypoxic cardiomyocytes or to the isolated intact heart during reperfusion after regional ischemia [ 69 ].…”
Section: Psychiatric and Cardiometabolic Mediators That Could Be Umentioning
confidence: 99%
“…CRF and urocortins also have cardioprotective effects that are mediated by cardiac CRF 2 receptors [ 67 ]. Urocortins 1, 2, and 3 are present in the heart, with the abundant expression of urocortins 2 and 3 in myocardium [ 68 ]. Urocortins are cardioprotective when added to post-ischemic/hypoxic cardiomyocytes or to the isolated intact heart during reperfusion after regional ischemia [ 69 ].…”
Section: Psychiatric and Cardiometabolic Mediators That Could Be Umentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] In the adult heart, CRF and/or its ligands have been found to be expressed in both animals and humans. More specifically, they were identified in the heart of rodents, 25 including rats 26,18 and mice, 21 dogs 27 and Tupaia belangeri. 28 In adult humans on the other hand, an immunohistochemical study revealed Ucn I immunoreactivity in myocytes of the normal heart, which was more intense in the diseased heart, indicating, together with evidence of its positive inotropic action, its possible role in the pathophysiology of cardiac hypertrophy or the failing heart.…”
mentioning
confidence: 99%